Presbyterian spirituality in southern Africa - Duncan, Graham (Scottish journal of theology, 2003)
Presbyterian spirituality in southern Africa has often been treated as non-existent, yet it is a vibrant reality which is at one and the same time catholic, evangelical and contextual. Founded in Christ alone, it holds the authority of scripture as normative and as the source of the unity of God's people, as can be seen in the way it derives from the marks of the church – the Word preached, the sacraments celebrated and discipline rightly exercised. It is relational and involves communing with God, others, oneself and the environment. While conscious of the early church tradition out of which it arises, it is continuous with that tradition and is open to the spiritual insights of other traditions. It demonstrates both catholic and evangelical emphases and is adaptable within the context of African spirituality. As a result, it has a broad church ethos marked by fluidity, tolerance and appreciation of those sources that enrich it.